Trend of Traditional Medicine and Ethnobotany Research: A Bibliometrics Analysis - Maulidatin Nanisfi; Susilawati Susilawati; Gunawan Gunawan; Didik Santoso; Lalu Japa (Current Educational Review, 2025)
The use of traditional medicine from herbs and natural ingredients has existed for a long time and goes alongside people's lives. So, this study aims to analyze the trend of scientific publications of traditional medicine research from 2015 to 2024. Bibliometric analysis was used, with the assistance of Dimensions.ai, Publish or Perish, and VOSviewer. The keywords used, both in Dimensions.ai and Publish or Perish, are “Traditional AND Medicine AND plant AND ethnobotany” with a time span of 2015-2024. The results showed that “pharmacology,” “herbalist,” and “medicinal plants” were some of the most frequently occurring keywords in this topic. In addition, in scientific publications, research trends also continue to evolve. More specifically, when the COVID-19 pandemic hit, there was a very significant increase in this topic.